Learners' Views Regarding the Use of Social Networking Sites in Distance Learning - Ozmen, Busra; Atici, Bunyamin (Athabasca Univ Press, 2014)
In this study, it was aimed to examine the use of learning management systems supported by social networking sites in distance education and to determine the views of learners regarding these platforms. The study group of this study, which uses a qualitative research approach, consists of 15 undergraduate students who resumed their education in Turkey. The data were gathered via a semi-structured interview form which consists of open-ended questions. Content analysis was used in the analysis of the data. According to the results of the study, it has been revealed within the scope of the course that the students have positive attitudes towards the use of social networking sites and distance education applications and these applications have positively affected the quality of communication between instructors and students. Furthermore, it was seen that the students made comments relating to the interesting aspects of the applications and the difference between distance education and face-to-face learning.
Keywords: Social networking sites; distance learning; learning management systems; Blackboard; CourseSites; Ning